2005
DOI: 10.1148/radiol.2351040269
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Tumor Growth with Combined Radiofrequency Ablation and Radiation Therapy in a Rat Breast Tumor Model

Abstract: Combined RF ablation and external-beam radiation therapy increased animal survival compared with that with either of the treatments alone or with no treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Viable tumor volumes for liposomal doxorubicin plus RF ablation, EXPERIMENTAL STUDIES: Chemoradionuclide Therapy with 186 Re-labeled Liposomal Doxorubicin Soundararajan et al 186 Re-liposomal doxorubicin did not result in a signifi cant decrease in average tumor volume or viable tumor volume compared to that with 186 Re-liposomal doxorubicin alone, four of six rats showed a decreasing tumor volume at 6 weeks. Possible reasons why we did not see complete tumor control as achieved by Horkan et al ( 24 ) with a combination of radiation therapy and RF ablation are as follows: (a) The tumor diameter in our study was twice that reported by Horkan et al (2.05 cm 6 0.24 vs 1.0 cm, respectively); (b) 186 Re radiation dose rate is not constant owing to clearance and decay and, hence, could allow for repair and repopulation of tumor cells; (c) the width of the remaining pepercentage injected dose of FDG could be used to measure therapeutic effi cacy in addition to changes in tumor volume in a preclinical model.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…Viable tumor volumes for liposomal doxorubicin plus RF ablation, EXPERIMENTAL STUDIES: Chemoradionuclide Therapy with 186 Re-labeled Liposomal Doxorubicin Soundararajan et al 186 Re-liposomal doxorubicin did not result in a signifi cant decrease in average tumor volume or viable tumor volume compared to that with 186 Re-liposomal doxorubicin alone, four of six rats showed a decreasing tumor volume at 6 weeks. Possible reasons why we did not see complete tumor control as achieved by Horkan et al ( 24 ) with a combination of radiation therapy and RF ablation are as follows: (a) The tumor diameter in our study was twice that reported by Horkan et al (2.05 cm 6 0.24 vs 1.0 cm, respectively); (b) 186 Re radiation dose rate is not constant owing to clearance and decay and, hence, could allow for repair and repopulation of tumor cells; (c) the width of the remaining pepercentage injected dose of FDG could be used to measure therapeutic effi cacy in addition to changes in tumor volume in a preclinical model.…”
Section: Discussionmentioning
confidence: 72%
“…RF ablation in combination with liposomal doxorubicin increased not only the ablation zone but also the drug accumulation in the tumor periphery, where recurrence occurs ( 19 ). Reduced tumor growth with RF ablation and external beam radiation therapy has also been reported ( 24 ) and attributed to the increased oxygenation in the peripheral tumor owing to hyperthermia, which sensitizes the tumor to radiation therapy. Considering the synergy achieved with RF ablation and chemotherapy or radiation therapy, we investigated the potential of RF ablation and chemoradionuclide therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations